Derecho Internacional de los Derechos Humanos y Derecho al agua: una perspectiva brasilera (2016)
This article discusses the recognition of the right to water in international human rights law and its implications. After demonstrating the disputes with respect to the interpretation of this right, it outlines the Brazilian contribution in regard to its incorporation in domestic law. Jurisprudence on the suspension of water supply due to non-payment is taken as a case study of the question of access to water and sanitation.